Students’ Loyalty Towards a Public Higher Education Institution in Mexico. - Figueroa Velázquez, Juan Gabriel; Garrido Vega, Miriam; Alcántara Hernández, Ruth Josefina (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To verify the relationship between the quality of the service and the CRM of students’ loyalty from a Higher Education Institution in Mexico. Reason why, quality management and customer relationship management [CRM] tools need to be applied in order to ensure a continuous improvement, so customers’ loyalty is achieved.MATERIAL AND METHOD: A quantitative, explanatory, and cross-sectional investigation was developed, through the approach of a model that met the requirements of convergent and discriminant validity, as well as an acceptable level of adjustment, through the structural equation modeling technique, using the Smart PLS 3 software.RESULTS: The CRM has a positive and significant relation, a weak one but present, regarding to students’ loyalty towards the university, which hypothesis 1 is supported by.CONCLUSIONS: Both proposed hypotheses in the model had a support. It was verified that the CRM and the quality of the service offered by the university in question are positively and significantly related to students’ loyalty.
Keywords: Quality of the service; Relationship Management (CRM); Loyalty; University.